A traffic equilibrium model with paid-parking search - Renger van Nieuwkoop; Kay Axhausen; Thomas F. Rutherford (ETH Zurich, CER-ETH - Center of Economic Research, 2016)
This paper describes a Wardropian traffic flow model integrated with a search model for paid parking. The occupancy rate influences the probability of finding on-street (curbside) or off-street (garage) parking spaces. We formulate the model as a mixed complementarity problem, which has the advantage that there is no need for a complete enumeration of all possible paths, and the model can be solved using readily available software. We analyze different parking policies in Zurich and find that changing the parking fee structure will lead to high efficiency gains. Incorporating household heterogeneity is not critical for the overall efficiency effects but shows important regressive, distributional effects.
Keywords: R41; R48; 330; parking modeling; traffic congestion; cruising for parking; on-street parking; mixed complementarity format; Verkehrsfluss; Parken; Gebühr; Simulation; Szenariotechnik; Zürich